Formulation and evaluation of extended release spheroids for antidepressant drug by MUPS - Kumar, Amrendra; Singh, Vikram; Juyal, Divya; Rawat, Geeta (Journal of Applied Pharmaceutical Research, 2014)
The extended release spheroids was Formulated using Ethyl Cellulose, Povidone and Triacetin as a Coating material and evaluated the effect of change in weight build up on drug release profile. Optimization of extended release coating by 19% build up of EC/PVP-K30 of formulation (F4), in which the formulation is formulated by Reservoir system and the drug release depends on coating thickness of EC/PVP-K30. As concentration of coating weight buildup increases. which increases the thickness of coating on the reservoir system hence release retarded and transformed into an extended release system.